Source rock characteristics, depositional setting and hydrocarbon generation potential of Cretaceous coals and organic rich mudstones from Gombe Formation, Gongola Sub-basin, Northern Benue Trough, NE Nigeria - Ayinla, H.A. (Elsevier B.V., 2017)
The ongoing exploration activities at the Maiganga coal mine uncover some missing gaps in the stratigraphy of the Late Cretaceous Gombe Formation. Therefore, there is a need to further investigate this sequence, including the organic facies variations and distributions of the coals, mudstones and sandy-shaly sediments in the Gombe Sandstone (Formation), Gongola Sub-basin, Northern Benue Trough of Northeastern Nigeria. Geochemical and petrographic methods were used to assess the organic matter source input, paleodepositional conditions, thermal maturity and hydrocarbon generation potential of the analysed Maiganga and Yaya-Ngari samples. Field observations showed four coal seams interbedded with mudstones and shales deposited in coarsening upward sequence of a deltaic environment. Evaluation based on the source rock analyses (SRA) reveals that Maiganga sedimentary facies is dominated by terrestrial source input of Type III kerogen. This is supported by the biomarker study suggesting land plant origin for the organic matter with minor lacustrine and marine influences, in Maiganga, that grades into predominantly mixed organic matter input of a transitional (terrestrial to marine) environment in the Yaya-Ngari area. This shows a progressive movement towards marine source input. Paleodepositional conditions of organic matters were sub-oxic to oxic in Maiganga, while the mixed organic matters in Yaya-Ngari were deposited in sub-oxic conditions. Based on organic petrology and bitumen extraction data, the Maiganga coal was distinctly observed to be immature of pre-oil generation window, while the Yaya-Ngari is in early oil generation window. These analysed sediments are mainly gas prone based on the dominance of Type III kerogen, although the presence of Type II/III kerogen supported by relatively higher HI may indicate gas/oil potential for the Maiganga coal. On the other hand, Type IV kerogen dominated the Yaya-Ngari samples. This suggests that these shales are gas prone or do not possess any hydrocarbon generation potential as indicated by the very low HI values. © 2017 Elsevier B.V.